2012
DOI: 10.1111/j.1574-6941.2012.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and distribution of segmented filamentous bacteria (SFB) in chicken gastrointestinal tract and their relationship with host immunity

Abstract: Uncultivable segmented filamentous bacteria (SFB) reside in the gastrointestinal (GI) tract of mammals and can boost the host immunity. Immunoglobulin A (IgA) from mother's milk has been previously shown to be a key factor in regulating SFB colonization. Because neonatal chicken cannot acquire IgA from maternal milk, they are a good model to examine the role of IgA in SFB colonization. Here, we used the fluorescent in situ hybridization (FISH) and quantitative PCR (qPCR) to monitor the colonization and distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 52 publications
(73 reference statements)
3
31
0
2
Order By: Relevance
“…Liao et al. () showed that total bacteria and segmented filamentous bacteria (SBF) in chicken gastrointestinal tract measured by FISH or qPCR were similar, with a slight increase in SBF population quantified by qPCR method. Some authors have shown that next‐generation sequencing (NGS) or qPCR are more precise to detect intestinal bacterial than FISH (Cleusix et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Liao et al. () showed that total bacteria and segmented filamentous bacteria (SBF) in chicken gastrointestinal tract measured by FISH or qPCR were similar, with a slight increase in SBF population quantified by qPCR method. Some authors have shown that next‐generation sequencing (NGS) or qPCR are more precise to detect intestinal bacterial than FISH (Cleusix et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A higher population of Lactobacillus is particularly associated with SFB-positive Taconic B6 mice. Liao et al (2012) reported that feeding Lactobacillus in drinking water can enhance the earlier colonization of SFB in neonatal chickens. In the current study, qPCR results showed the populations of the total bacteria and other indigenous bacteria to be higher in SFB-positive infants than in SFB-negative infants.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution and diversity of human SFB Y Yin et al the B cells of the host, affects the SFB colonization profoundly (Ohashi et al, 2006;Liao et al, 2012). For mice, the peak number of SFB in the ileum coincides with the window between weaning and the initiation of SIgA self-production.…”
Section: Discussionmentioning
confidence: 99%
“…SFB are found principally in the ileal mucus with some presence in ileal content (63) although there is one report of SFB in the caecal tonsils (64). SFB appear during the first week of life, reaching peak abundance between 9 and 14 d.p.h before declining (63,64). The pattern of colonization varies greatly among individual birds, especially at an early age.…”
Section: Candidatus Arthromitus: Colonization and Immune Developmentmentioning
confidence: 99%